Supporting Inuit food sovereignty through collaborative research of an at-risk caribou herd - Hanke, Andrea; Niptanatiak Dumond, Amanda; Di Francesco, Juliette; Adams, Cindy Lou; Milton, Terry; Leclerc, Lisa-Marie; Maksagak, Beverly; Nathoo, Rosemin; Roberto-Charron, Amélie; Blue, Gwendolyn; Kutz, Susan (Frontiers in Sustainable Food Systems, 2024)
Introduction Climate change is increasing vulnerability to food insecurity and biodiversity loss for many Indigenous Peoples globally. For Inuit, food sovereignty is one expression of Indigenous self-determination, and it includes the right of all Inuit to define their own conservation policies. Caribou conservation is particularly pertinent because of the central role caribou play in Inuit food systems. The “Dolphin and Union” (DU) caribou herd is a critical component of Inuit food systems in the Canadian Arctic and has declined by 89% in 2020 (3,815) from the peak measured by aerial survey in 1997 (34,558). Methods Our first objective was to identify insights about this herd from and with Inuit Qaujimajatuqangit (knowledge). Using thematic analysis, we created a collective account on the DU caribou herd through a research partnership among Indigenous knowledge keepers, government, and academia. Our second objective was to put our findings into the broader literature on the DU caribou herd and connect isolated data on their abundance and distribution. Results We found understanding Inuit knowledge of caribou meant situating harvesters’ knowledge within their family history, harvesting methods, conservation ethics, and in relation to other harvesters. Through this framework, we conceptualized Inuit-described metrics of caribou status, resulting in three sub-themes of caribou trends over time – their abundance, distribution, and health, − and ending with conservation concerns and potential actions. The synthesized data indicated that the overall population size increased since 1990s and then decreased after 2000s alongside a range contraction. Our results add value to co-management literature by (1) articulating Inuit-described metrics of a population decline that inform continued monitoring and incorporation of these metrics into management planning and (2) synthesizing data from various studies on the DU caribou herd abundance and distribution that assists management to make informed conservation decisions based on Inuit and Western knowledge. Discussion Results from this research contribute to understanding the six dimensions of environmental health, i.e., availability, stability, accessibility, health and wellness, Inuit culture, and decision-making power and management relating to caribou. The results contribute information that is used by to support environmental health, i.e., knowledge systems, policy, and co-management relating to caribou. Thus, this collaborative research study supports the expression of Inuit food sovereignty through caribou conservation.